Prevalence of substance use and related factors in patients seeking treatment for obesity - Yaluğ, İrem; Özmen, Mine; Tufan, Ali Evren; Yumuk, Volkan (Journal of Dependence, 2005)
Objective: Obese individuals who self present for treatment are commonly found to have associated psychopathology. This study is designed to clarify the prevalence and predictors of substance use in an obese population undergoing treatment in a university hospital.Method: This is a cross sectional study which evaluated 169 patients being followed for treatment of obesity in Istanbul University Cerrahpasa Medical Faculty, Department of Endocrinology, for comorbid psychopathology, by means of structured interviews (SCID I and II). Patients with Body Mass Index (BMI) >25.0 are defined as obese and those with BMI between 25.0-29.9 are divided as stage I, the remainder being stage II. Data were analysed with descriptive statistics, binomial regression analysis and chi square test. A difference at the level of P
Keywords: obesity; dopamine; nicotine; alcohol; body mass index